Notes to Philosophy 167: Class 3 -- Kepler's Astronomia Nova: The Orbit of Mars -- Part 9. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: "Phase 3": Bisect the Eccentricity of the Earth-Sun Orbit -- "Phase 3" Continued: the Area Rule.; Generally corresponds to the video segment: Class 3, Part 9.